Effect Of Single Live Trap Rat Trap Model And Sherman Snap Trap Modification On The Number Of Mice Trapped In Pt.X Kitchen - Saffa Sallina, Vianca; Bambang Purnama, Lubis; Iqbal, Muhamad (Jurnal Sanitasi Profesional Indonesia, 2024)
Rats become pests that cause losses. PT. X has a kitchen to serve lunch to all employees and in the kitchen there are rats with a trap success rate of 4% and losses are experienced such as some food stocks in the kitchen being bitten by rats so that the food stocks cannot be reused. The purpose of this study is to determine the effect of the modified Sherman trap model of snap trap and single live trap on the number of rats trapped in the PT.X kitchen. This type of research is an experimental research with a post-test only research design. The population of all rats in the kitchen area of PT.X. The treatment given was 2 treatments, namely single live trap treatment and Sherman snap trap treatment. The data collection technique counted the number of rats trapped, the number of traps set is three Sherman snap traps and three single live traps set for 5 days with shrimp paste bait. The number of rats caught in the Sherman snap trap was 4 with a catch rate of 6%, in the single live trap there were no rats caught. The results of the study after analysis using the Mann-Whitney test showed that the P-value was 0.014 < α (0.05), meaning that there was a significant difference between the two groups of data. The implication of this research is that the kitchen manager of PT. X can use a Sherman snap trap for trapping activities in the kitchen. The trapping activities are carried out with suggestions to vary the layout of the trap placement, replacement of bait that is more varied according to the type of food preferred by the rats, namely tubers such as cassava, sweet potatoes or can use bait of corn and grilled coconut.